2011
DOI: 10.1002/smll.201100191
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan‐Functionalized Graphene Oxide as a Nanocarrier for Drug and Gene Delivery

Abstract: The covalent functionalization of graphene oxide (GO) with chitosan (CS) is successfully accomplished via a facile amidation process. The CS-grafted GO (GO-CS) sheets consist of about 64 wt.% CS, which imparts them with a good aqueous solubility and biocompatibility. Additionally, the physicochemical properties of GO-CS are studied. As a novel nanocarrier, GO-CS is applied to load a water-insoluble anticancer drug, camptothecin (CPT), via π-π stacking and hydrophobic interactions. It is demonstrated that GO-CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
484
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 835 publications
(515 citation statements)
references
References 61 publications
14
484
2
4
Order By: Relevance
“…Upon mixing GO into CS solution, irregular shape of nanocomposites was observed as shown in Figure 4(b). Similar morphology was also reported by Bao et al [16], in which CS-GO appear to be coarse and some protuberances could be seen on the surface, which mainly were generated from the polymer wrapping and folding. Figure 4(c) shows formation of small, rounded, and smooth surface of CS-GO-DsiRNA nanocomposites.…”
Section: Morphological Analysissupporting
confidence: 88%
See 3 more Smart Citations
“…Upon mixing GO into CS solution, irregular shape of nanocomposites was observed as shown in Figure 4(b). Similar morphology was also reported by Bao et al [16], in which CS-GO appear to be coarse and some protuberances could be seen on the surface, which mainly were generated from the polymer wrapping and folding. Figure 4(c) shows formation of small, rounded, and smooth surface of CS-GO-DsiRNA nanocomposites.…”
Section: Morphological Analysissupporting
confidence: 88%
“…GO analysed under an electron microscope appeared to be in layers of lateral dimension sheets with sharp edges (Figure 4(a)). It was reported that GO sheets exist with very sharp edges and flat surfaces [16] that coincided with the GO produced in current study. Besides, large surface area of GO sheets is usually utilised as support for growth and stabilisation of nanoparticles [30].…”
Section: Morphological Analysissupporting
confidence: 86%
See 2 more Smart Citations
“…[5][6][7] In studies of drug carrier and disease therapy, most researchers have been paying great attention to therapy of graphene and its derivatives to tumor. [8][9][10][11][12][13] Ma et al [14] constructed a targeting GO drug carrier using folic acid conjugated bovine serum albumine (FA-BSA) as both the stabilizer and targeting agent, then used as a targeting drug delivery carrier to treat human breast cancer cells.…”
Section: Introductionmentioning
confidence: 99%